Identification of candidate genes involved in Witches’ broom disease resistance in a segregating mapping population of Theobroma cacao L. in Brazil - Royaert, Stefan (BMC Genomics, 2016)
BACKGROUND: Witches’ broom disease (WBD) caused by the fungus Moniliophthora perniciosa is responsible for considerable economic losses for cacao producers. One of the ways to combat WBD is to plant resistant cultivars. Resistance may be governed by a few genetic factors, mainly found in wild germplasm. RESULTS: We developed a dense genetic linkage map with a length of 852.8 cM that contains 3,526 SNPs and is based on the MP01 mapping population, which counts 459 trees from a cross between the resistant ‘TSH 1188’ and the tolerant ‘CCN 51’ at the Mars Center for Cocoa Science in Barro Preto, Bahia, Brazil. Seven quantitative trait loci (QTL) that are associated with WBD were identified on five different chromosomes using a multi-trait QTL analysis for outbreeders. Phasing of the haplotypes at the major QTL region on chromosome IX on a diversity panel of genotypes clearly indicates that the major resistance locus comes from a well-known source of WBD resistance, the clone ‘SCAVINA 6’. Various potential candidate genes identified within all QTL may be involved in different steps leading to disease resistance. Preliminary expression data indicate that at least three of these candidate genes may play a role during the first 12 h after infection, with clear differences between ‘CCN 51’ and ‘TSH 1188’. CONCLUSIONS: We combined the information from a large mapping population with very distinct parents that segregate for WBD, a dense set of mapped markers, rigorous phenotyping capabilities and the availability of a sequenced genome to identify several genomic regions that are involved in WBD resistance. We also identified a novel source of resistance that most likely comes from the ‘CCN 51’ parent. Thanks to the large population size of the MP01 population, we were able to pick up QTL and markers with relatively small effects that can contribute to the creation and selection of more tolerant/resistant plant material. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2415-x) contains supplementary material, which is available to authorized users.